IMPLEMENTATION STRATEGY OF GEOGRAPHY LEARNING PROCESS BASED ON CURRICULUM 2013 IN BACKWARD REGIONS (Case Study in Lebak Regency, Banten) - Rahmatia Rahmatia; Ahmad Yani; Nandi Nandi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
In the Curriculum 2013, teachers play an important role in shaping the character and competence of learners according to the character of each individual, who must be creative in sorting and choosing, and developing methods and learning, and must appear in front of the learners. Therefore, teachers need to design appropriate learning to realize attitude-based learning, skills, and knowledge. Successful implementation of the Curriculum 2013 is certainly a challenge for backward regions to carry it out properly and in accordance with established standards. This study aims to determine implementation strategy of geography learning process based on Curriculum 2013 in backward regions. This research uses qualitative approach with descriptive method. The principal participants in this study were Geography teachers at the State Senior High School who have implemented the Curriculum 2013 in backward region in Lebak Regency, Banten. Meanwhile, the participants of the base are learners and academic supervision. The research instruments are observation, interview, and document review.